2009
DOI: 10.1007/s00535-009-0056-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of OATP1B3 determines uptake of Gd-EOB-DTPA in hepatocellular carcinoma

Abstract: Uptake of Gd-EOB-DTPA in HCC is determined by expression of OATP1B3 rather than by tumor differentiation or bile production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
308
3
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(326 citation statements)
references
References 16 publications
13
308
3
2
Order By: Relevance
“…Bile production is most typically observed in relatively well-differentiated HCCs as compared to poorly differentiated HCCs, especially in moderately differentiated HCCs as compared to well-differentiated HCCs and appear with a green color in resected specimens, so called green hepatoma (22). Our results show that although macroscopically, most non-hypointense areas of HCCs on gadoxetic acid-enhanced hepatobiliary-phase images may be associated with an area with a green color, no microscopic difference of bile production between non-hypointense and hypointense areas of an HCC was found, which is similar to a finding of a previous report (21). Our results also show the green color of an HCC in a resected specimen may not indicate bile production.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Bile production is most typically observed in relatively well-differentiated HCCs as compared to poorly differentiated HCCs, especially in moderately differentiated HCCs as compared to well-differentiated HCCs and appear with a green color in resected specimens, so called green hepatoma (22). Our results show that although macroscopically, most non-hypointense areas of HCCs on gadoxetic acid-enhanced hepatobiliary-phase images may be associated with an area with a green color, no microscopic difference of bile production between non-hypointense and hypointense areas of an HCC was found, which is similar to a finding of a previous report (21). Our results also show the green color of an HCC in a resected specimen may not indicate bile production.…”
Section: Discussionsupporting
confidence: 88%
“…In another report with 83 HCCs, 2 well-differentiated HCCs, 5 moderately differentiated HCCs, and 1 poorly differentiated HCC exhibited iso-intensity or hyperintensity relative to the surrounding liver parenchyma (11). Recently, Narita et al (21) reported that hyperintense lesions were found in 6 of 22 HCCs, in which all cases were moderately differentiated. Our study showed no correlation between tumor differentiation of an HCC and the uptake of gadoxetic acid as previously reported (11,20,21).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These dual-action contrast agents permit evaluation of tumor vascularity in the early dynamic imaging-phase and tumor uptake of the contrast agent via sodium-independent organic anion transporters in the delayed hepatocyte-phase [12]. In nodules not demonstrating the characteristic arterial enhancement followed by washout, the absence of tumor enhancement in the hepatocyte phase is also suggestive of HCC [13].…”
mentioning
confidence: 99%